Identification and in silico prediction of metabolites of tebufenozide derivatives by major human cytochrome P450 isoforms. Issue 9 (1st May 2020) - Edamatsu, Hiroaki; Yagawa, Masataka; Ikushiro, Shinichi; Sakaki, Toshiyuki; Nakagawa, Yoshiaki; Miyagawa, Hisashi; Akamatsu, Miki
Graphical abstract: Highlights: In silico prediction of tebufenozide derivatives metabolites by CYPs was performed. A docking simulation and hydrogen atom abstraction energy estimation were used. The production rate of the metabolites by CYP3A4 was quantitatively analyzed. The obtained quantitative model was applied to predict the sites of metabolism. Abstract: Cytochrome P450 (CYP) enzymes constitute a superfamily of heme-containing monooxygenases. CYPs are involved in the metabolism of many chemicals such as drugs and agrochemicals. Therefore, examining the metabolic reactions by each CYP isoform is important to elucidate their substrate recognition mechanisms. The clarification of these mechanisms may be useful not only for the development of new drugs and agrochemicals, but also for risk assessment of chemicals. In our previous study, we identified the metabolites of tebufenozide, an insect growth regulator, formed by two human CYP isoforms: CYP3A4 and CYP2C19. The accessibility of each site of tebufenozide to the reaction center of CYP enzymes and the susceptibility of each hydrogen atom for metabolism by CYP enzymes were evaluated by a docking simulation and hydrogen atom abstraction energy estimation at the density functional theory level, respectively. In this study, the same in silico prediction method was applied to the metabolites of tebufenozide derivatives by major human CYPs (CYP1A2, 2C9, 2C19, 2D6, and 3A4). In addition, the production rate of the metabolites by CYP3A4 was quantitively analyzed by frequency based on docking simulation and hydrogen atom abstraction energy using the classical QSAR approach. Then, the obtained QSAR model was applied to predict the sites of metabolism and the metabolite production order by each CYP isoform.